2023
DOI: 10.3389/fgene.2023.1186862
|View full text |Cite
|
Sign up to set email alerts
|

A novel anoikis-related gene prognostic signature and its correlation with the immune microenvironment in colorectal cancer

Abstract: Background: Anoikis is a type of apoptosis associated with cell detachment. Resistance to anoikis is a focal point of tumor metastasis. This study aimed to explore the relationship among anoikis-related genes (ARGs), immune infiltration, and prognosis in colorectal cancer (CRC).Methods: The transcriptome profile and clinical data on patients with CRC were retrieved from The Cancer Genome Atlas and Gene Expression Omnibus databases. Patients were divided into two clusters based on the expression of ARGs. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…8 e–g). The predicted clinicopathological characteristics were consistent with previous literature analyzed by TCGA COAD/READ cohort 35 .
Figure 8 Establishment of a nomogram signature based on clinicopathological characteristics and risk scores.
…”
Section: Resultssupporting
confidence: 90%
“…8 e–g). The predicted clinicopathological characteristics were consistent with previous literature analyzed by TCGA COAD/READ cohort 35 .
Figure 8 Establishment of a nomogram signature based on clinicopathological characteristics and risk scores.
…”
Section: Resultssupporting
confidence: 90%
“…In the study by Xiao et al 53 , the LASSO regression method was also used to identify 25 ARGs related to CRC prognosis, which is completely different from the 7 genes obtained in this study. In their study, 540 CRC sample from TCGA were selected, whereas in this study, we selected dataset from both TCGA and GEO.…”
Section: Discussionmentioning
confidence: 61%
“…Conversely, they found a negative correlation between anoikis scores and tumor-infiltrating lymphocytes (TIL) and Th1 levels [ 31 ]. According to the report by Xiao et al [ 32 ], in cases of colorectal cancer, there was a positive relationship observed between the risk score and regulatory T cells. On the other hand, a negative correlation was found between the risk score and activated dendritic cells, resting memory CD4 T cells, as well as eosinophils [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the report by Xiao et al [ 32 ], in cases of colorectal cancer, there was a positive relationship observed between the risk score and regulatory T cells. On the other hand, a negative correlation was found between the risk score and activated dendritic cells, resting memory CD4 T cells, as well as eosinophils [ 32 ]. In our research, we observed that risk scores were positively correlated with T cells gamma delta, eosinophils, neutrophils cells, and negatively correlated with M0 macrophages.…”
Section: Discussionmentioning
confidence: 99%